2017
DOI: 10.1128/aem.00457-17
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Dependent Enzyme Catalyzes the Initial Step in Biodegradation of N -Nitroglycine by Variovorax sp. Strain JS1663

Abstract: Nitramines are key constituents of most of the explosives currently in use and consequently contaminate soil and groundwater at many military facilities around the world. Toxicity from nitramine contamination poses a health risk to plants and animals. Thus, understanding how nitramines are biodegraded is critical to environmental remediation. The biodegradation of synthetic nitramine compounds such as hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX) has been studied for decades, but little is known about the cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Interestingly, some of these strains are toxic-compound degraders (e.g., Achromobacter xylosoxidans A8 and Variovorax sp. strain JS1663 (40,41), human pathogens (e.g., Bordetella pertussis Tohama I and Bordetella bronchiseptica RB50) (42), and nematicidal bacteria (e.g., A. faecalis ZD02) (43), whereas other strains represent typical soil bacteria (e.g., Pseudomonas), plant rhizosphere-associated bacteria (e.g., Bradyrhizobium), arctic bacteria (Octadecabacter arcticus 238) (44), and Antarctic bacteria (Hoeflea sp. strain IMCC20628) (45).)…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, some of these strains are toxic-compound degraders (e.g., Achromobacter xylosoxidans A8 and Variovorax sp. strain JS1663 (40,41), human pathogens (e.g., Bordetella pertussis Tohama I and Bordetella bronchiseptica RB50) (42), and nematicidal bacteria (e.g., A. faecalis ZD02) (43), whereas other strains represent typical soil bacteria (e.g., Pseudomonas), plant rhizosphere-associated bacteria (e.g., Bradyrhizobium), arctic bacteria (Octadecabacter arcticus 238) (44), and Antarctic bacteria (Hoeflea sp. strain IMCC20628) (45).)…”
Section: Resultsmentioning
confidence: 99%
“…In C. sinensis -infected individuals, the higher relative abundance of Enterococcus might not be conducive to recovery from clonorchiasis. Variovorax , an important environmental taxa ( Thomas et al, 2017 ; Woo et al, 2017 ), has been reported to produce nitramine ( Mahan et al, 2017 ), which is harmful to humans and animals. This taxa was only detected in the C. sinensis infected groups, however, it was not correlated with EPG.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some of these strains are toxic compound degraders (e.g., Achromobacter xylosoxidans A8 and Variovorax sp. JS1663) (36, 37), human pathogens (e.g., Bordetella pertussis Tohama I and Bordetella bronchiseptica RB50) (38), and nematicidal bacteria (e.g., A. faecalis ZD02) (39), whereas other strains represent typical soil bacteria (e.g., Pseudomonas ), plant rhizosphere-associated bacteria (e.g., Bradyrhizobium ), arctic bacterium ( Octadecabacter arcticus 238) (40), and antarctic bacterium ( Hoeflea sp. IMCC20628) (41).…”
Section: Resultsmentioning
confidence: 99%